The Problems of E-Ticketing From Legal Perpective - Luhukay, Roni Sulistyanto; Gusti Fadhil Fithrian Luthfan; Edy Chrisjanto (Fakultas Hukum Universitas Widya Mataram, 2023)
The problems faced in the development of an electronic system use CCTV to carrying out the function of monitoring and enforcing traffic were : (1) Traffic and legal compliance awareness in paying fines. (2) Public considers about failures in building a good law enforcement structure. (3) Because people who violate it feel afraid to pay STNK, it potyentialy reduction in non-tax state income through the e-ticket policy. (4) misdirect in sent ticket letters, because many vehicles are purchased by people who administratively still with old ownwer. This research uses nomative legal research methods. This study discusses about the urgency legal certainty of e-tickets, including certainty about the violators, regarding to amount and what kind of violaion which has been included on the blue slip. In terms of justice, traffic violators who commit the same offense will receive the same penalty or fine without discrimination, E-tickets are also a form of transparency and professionalism of police officers in law enforcement, to prevent issues of illegal levies (Pungli) by unscrupulous individuals. Characteristics of e-ticket regulations in criminal law framework more focuses on fines than the concept of non-compliance in driving. Articles contained in Law no. 22 of 2009 concerning Road Traffic and Transportation has not been implemented in a real way especially sanctions for revoking driving licenses